2016
DOI: 10.22161/ijaers/3.10.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre and Post Emergence Herbicides to Weeds Control in Corn Field

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Corn plants were recovered lately from the symptoms of injuries. The ability of corn plants to recover from bleaching symptoms was also stated in previous studies that described the injury of maize plants due to the application of premixed herbicide atrazine and mesotrione immediately recovered a few weeks after application 21,32 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Corn plants were recovered lately from the symptoms of injuries. The ability of corn plants to recover from bleaching symptoms was also stated in previous studies that described the injury of maize plants due to the application of premixed herbicide atrazine and mesotrione immediately recovered a few weeks after application 21,32 .…”
Section: Discussionsupporting
confidence: 58%
“…The highest efficacy was found when the application time was conducted at a very early postemergence (2 WAP). In this treatment, the growth stage of corn has not covered yet the planting area so that the targeted spraying on the weed surface can be reached properly 32 . On the other hand, a light injury of corn was observed if the application time was conducted at a very early postemergence (2 and 3 WAP) because the corn height was still lower than the height of the nozzle spray.…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference in grain and straw yields of maize was observed might be due to minimum weed seed bank and eradication of weeds providing a healthy environment for crop plant growth (Riaz et al, 2007). Totally, the results showed that application of herbicide led to a reduction of damages caused by weeds, also, it was determined that using of 2,4 D Ethyl Ester 38% EC had the highest effect on weed control in comparison to control resulted in increased straw and grain yield (Baniasadi, 2016).…”
Section: Crop Yieldmentioning
confidence: 98%
“…by controlling wide range of weeds in the maize crop (Amare et al, 2015;Baniasadi, 2016;Kumar et al, 2017).…”
Section: Weed Density and Dry Weightmentioning
confidence: 99%